THE PR 2.0 USAGE AND UTILIZATION IN RESOURCE FINDING OF WOMAN AID ORIENTED NON PROFIT ORGANIZATIONS IN TURKEY - Ozturk, E. Sahra (European Scientific Journal, ESJ, 2013)
The subject of Public Relations 2.0 (PR 2.0) has emerged with the Web 2.0 applications refering online applications such as Web sites, blogs, social media sites. Today, online applications are integral parts of modern society. They can also be accepted as the most recent social instruments of communication. Non Profit Organizations (NPOs) try to keep up with the innovations and benefit from the PR 2.0 applications. But, when it is regarded to NPOs in Turkey, although PR 2.0 applications are useful at the present time in almost all sectors, the woman aid oriented NPOs are not informed sufficiently about the benefits of these applications or do not prefer to use it, at all. Because of this reason, this study analyses PR 2.0 utilization of woman aid oriented NPOs in Turkey and questions whether they utilize it in resource finding. It is aimed in the study to search the woman aid oriented NPOs in Turkey through the two indicator questions; â€œDo woman aid oriented NPOs in Turkey use PR 2.0?â€ and â€œ Do they benefit from PR 2.0 in resource finding?â€. The study uses both qualitative and quantitative methods. Library sources, online datas and the survey data are used to answer the research questions. Research findings indicate that woman aid oriented NPOs in Turkey do not use the PR 2.0 properly and they do not benefit it in resource finding. Mostly they prefer traditional ways instead of trying the innovative ways. They keep using efficiently the traditional public relations ways both in their communication and resource finding processes.